Analysis of spatial components in building-garden-garden-road relationship: Trabzon, Yavuz Selim Boulevard example - Emine Tarakcı Eren; Cengiz Acar (İstanbul Üniversitesi Orman Fakültesi Dergisi, 2017)
The objective of this study is to analyze the urban area that emerged after construction of Yavuz Selim Boulevard, in Trabzon City, Turkey. Cities contain many functional elements, such as businesses, gardens, parks, shops, medical and educational institutions, and transportation arteries such as roads, streets, boulevards, and avenues, which enable contact between all elements of a city. Cities change culturally, economically, and also physically and ecologically. However, although urbanization provides convenience for people, it also has disadvantages, such as causing a loss of natural features within the living space. In particular, changes made without appropriate design and planning disrupt the spatial integrity. Ninety-two buildings are situated on the south and north sides of Yavuz Selim Boulevard. In this study, the front and frontages of buildings and the area of road associated with each building are examined and spatial components are determined. In addition, building function and number of storeys, the differences between elevations of the road and entrances of buildings, road width, and the structural and botanical landscape elements are determined.